A single nucleotide change in a core promoter is involved in the progressive overexpression of the duplicated CYP9M10 haplotype lineage in Culex quinquefasciatus - Itokawa, Kentaro; Komagata, Osamu; Kasai, Shinji; Tomita, Takashi (Insect biochemistry and molecular biology, 2015)
Although the importance of cis-acting mutations on detoxification enzyme genes for insecticide resistance is widely accepted, only a few of them have been determined as concrete mutations present in genomic DNA till date. The overexpression of a cytochrome P450 gene, CYP9M10, is associated with pyrethroid resistance in the southern house mosquito Culex quinquefasciatus. The haplotypes of CYP9M10 exhibiting overexpression (resistant haplotypes) belong to one specific phylogenetic lineage that shares high nucleotide sequence homology and the same insertion of a transposable element. Among the resistant haplotypes, allelic progression involving an additional cis-acting mutation and gene duplication evolved a CYP9M10 haplotype associated with extremely high transcription and strong pyrethroid resistance. Here we show that a single nucleotide substitution G−27A, which is located near the transcription start site of CYP9M10, is involved in the progression of the duplicated haplotype lineage. The deletion of a 7-bp AT-rich sequence that includes nucleotide −27 inhibited the initiation of transcription from the original transcriptional initiation site. The mutation was suspected to reside within a core promoter, TATA-box, of CYP9M10. [Display omitted] •The overexpression of a cytochrome P450 gene CYP9M10 is correlated with pyrethorid resistance in Culex quinquefasciatus.•At least two cis-acting mutations and gene duplication are involved in the most overexpressing CYP9M10 haplotype.•Reporter assay in this study indicated that G−27A mutation in promoter region of CYP9M10 increased the expression of CYP9M10.•The G−27A mutation was the second cis-acting mutation in the allelic progression of the CYP9M10 haplotype.•The −27 nucleotide was considered to be included in a core promoter, TATA-box, of CYP9M10.